Motivational factors for adult amateur volleyball athletes - Aniszewski, Ellen (2024)
Volleyball is one of the most popular recreational and competitive sports in the world. The aim of this study was to investigate the main factors that motivate amateur volleyball players and to determine whether they differ between sexes. The sample consisted of 200 athletes, with a mean age of 26.5 ± 5.5 years, from amateur teams of the adult category who participated in the Rio de Janeiro State Volleyball League in 2018. The Participation Motivation Questionnaire (PMQ), adapted and validated for Brazil, was used for this purpose. The results indicated that affiliation, health, technical improvement and physical conditioning are the most important factors for practitioners, demonstrating the predominance of self-regulated intrinsic reasons, which contribute to lasting bonds with the sports practice.